Indonesia’s Approach on Cyberattack Attribution through its Foreign Policy - Citra Yuda Nur Fatihah (Universitas Pelita Harapan, 2022)
It is clear that cybersecurity has now become a matter of increasing concern for Indonesian citizens, the private sector and the Indonesian government. Indonesia is ranked among the top countries from which cyberattacks are launched, while at the same time is itself very vulnerable to cyberattack. Indeed, Indonesia is currently in the early stages of developing a national cybersecurity strategy. The legal framework for cybersecurity in Indonesia is still weak that there is no clear classified security law or policy, and security practices are spread across different legislation while there are no specific cybersecurity provisions in place. Indonesia also lacks of national policy and strategy when it seeks to defend itself against cyberattack, particularly those hacking activities from foreign actors or state-sponsored groups. While majority of states in the world have two different approaches on cyberattack attribution from the context of sovereignty in international law, those applied sovereignty as a rule and as a principle, Indonesia has never stated clearly its position. Therefore, based on the analysis on how Indonesia’s approach on sovereignty through its foreign policy, from the perspectives of diplomacy practices and national policies, relevant sovereignty-violation cases, and its international framework and cooperation on cybersecurity, we may conclusively view that Indonesia appears to endorse the sovereignty-as-a-rule position, where it upholds the principle of respect for state sovereignty on cyberspace.